2021
DOI: 10.1002/anie.202109749
|View full text |Cite
|
Sign up to set email alerts
|

Targetable Conformationally Restricted Cyanines Enable Photon‐Count‐Limited Applications**

Abstract: Cyanine dyes are exceptionally useful probes for ar ange of fluorescence-based applications,b ut their photon output can be limited by trans-to-cis photoisomerization. We recently demonstrated that appending ar ing system to the pentamethine cyanine ring system improves the quantum yield and extends the fluorescence lifetime.H ere,w er eport an optimizeds ynthesis of persulfonated variants that enable efficient labeling of nucleic acids and proteins.Wedemonstrate that ab ifunctional sulfonated tertiary amide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…However, cyanine dyes feature photo-isomerization pathways, which lead to energy dissipation after excitation, low quantum yield, and weak fluorescence signal. ,, Therefore, Cy3B and Cy5B have been developed as the conformationally locked versions of Cy3 and Cy5, respectively, to prevent photo-isomerization. Cy3B and Cy5B exhibit boosted fluorescence properties than their counterparts. , The compromised photon emission of Cy3B and Cy5B with the Maleimide-thiol linkage prompted us to test the POD strategy on these conformational rigidified cyanine dyes. Thus, we synthesized POD-derived Cy3B and Cy5B and characterized their properties on DNA and proteins (Figures C,D, S13, and S14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cyanine dyes feature photo-isomerization pathways, which lead to energy dissipation after excitation, low quantum yield, and weak fluorescence signal. ,, Therefore, Cy3B and Cy5B have been developed as the conformationally locked versions of Cy3 and Cy5, respectively, to prevent photo-isomerization. Cy3B and Cy5B exhibit boosted fluorescence properties than their counterparts. , The compromised photon emission of Cy3B and Cy5B with the Maleimide-thiol linkage prompted us to test the POD strategy on these conformational rigidified cyanine dyes. Thus, we synthesized POD-derived Cy3B and Cy5B and characterized their properties on DNA and proteins (Figures C,D, S13, and S14).…”
Section: Resultsmentioning
confidence: 99%
“…For most of these techniques, including single-molecule fluorescence resonance energy transfer (smFRET), single-molecule tracking, single-molecule localization microscopy (SMLM), , stimulated emission depletion (STED) , microscopy, and MINFLUX nanoscopy, a central demand is to obtain sufficient photons from individual fluorophores to achieve long-time imaging with high temporal resolution and/or high spatial resolution. At the same time, the modern fluorophore palette has constantly been expanding and upgrading to meet the growing demand for the photon output. Notable strategies include sulfonation, auxochrome optimization, DNA FluoroCube, and conformational restriction. In parallel with these approaches in dye chemistry, photoprotective agents and oxygen scavengers are routinely applied to increase the photostability of fluorophores. A particularly interesting initiative in the past decade has been to covalently conjugate photostabilizers, including cyclooctatetraene (COT), nitrobenzyl alcohol (NBA), and Trolox, to fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…It was, however, photoactivatable after incubation in NaBH 4 ‐containing buffer and was used for TRABI‐BP SMLM. Cy5B has since been used in PALM and shown to give significantly improved resolution (13.5 nm) compared to Cy5 (17.7 nm) [22a] . These reductively caged and caging‐group‐free (PaX) strategies avoid the release potentially biologically active or toxic molecules into the sample.…”
Section: Photochemical Mechanisms Of Fluorophores Used In Smlmmentioning
confidence: 99%
“…[21] In addition to the crucial ability of fluorophores to switch between bright (emissive) and dark (non-emissive) states, other fluorophore properties such as photon count, fluorophore stability, and duty cycle influence the localization precision of individual molecules as well as the resolution achieved. [22] A wide range of switchable fluorophores have been utilized for SMLM, including synthetic organic fluorophores and fluorescent proteins. Small-molecule fluorophores are generally preferred over fluorescent proteins because they tend to have higher quantum yields and greater photostability.…”
Section: Single Molecule Localization Microscopymentioning
confidence: 99%
“…The rich photochemistry of broadly used cyanine probes has enabled applications ranging from super-resolution microscopy to in vivo drug delivery. We recently found that the hypsochromic photoconversion (i.e., “photoblueing”) of cyanines involves a previously uncharacterized phototruncation reaction (Figure a). , This chemistry, mediated by singlet oxygen, involves the formal excision of ethene diradical from the polymethine chain resulting in the two-carbon truncated product . We demonstrated that cyanine phototruncation could be applied for single-molecule localization microscopy (SMLM) applications .…”
mentioning
confidence: 91%